Productivity limiting impacts of boron deficiency, a review - Benjavan Rerkasem (2020)
© 2020, Springer Nature Switzerland AG. Background: In the almost century since the establishment of boron (B) as an essential plant nutrient, its roles in plant growth and development have been identified, and the mechanism for B transportation explained. Scope: This review relates the yield response of crops, measured as B efficiency i.e. productivity when B is limiting relative to when it is not, to the B supply logistics and requirement of different tissues and organs. Conclusions: Yield is depressed by B deficiency in graminaceous cereals primarily by impaired development and function of the stamen and pistil, but in dicots the adverse effects are expressed as structural damage to various organs. Boron-efficient cereal genotypes are readily identifiable by their successful grain set under limited B, while the quantitative trait loci associated with B efficiency provide a useful selection tool for dicots. The relevance to breeding for B efficiency of the numerous BOR1 and NIP genes controlling active B transport identified in many crops will depend on how close their up-regulation in a deficiency is associated with B efficiency. Understanding of the yield impact of B deficiency is useful in dealing with crop choice and the management of germplasm and B fertilizer.